1994
DOI: 10.1021/ac00085a019
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Zone Electrophoresis Separations of Basic and Acidic Proteins Using Poly(vinyl alcohol) Coatings in Fused Silica Capillaries

Abstract: Poly(vinyl alcohols) (PVA) of a molecular weight of about 50 000 were applied to the modification of fused silica surfaces for the separation of large charged molecules such as proteins.Basic and acidic proteins could be separated in PVA-modified capillaries at highly optimized and analytically suitable performance with regard to efficiency, zone symmetry, and resolution. PVA can be used in the "dynamic" mode as an additive to the buffer medium or as a water-insoluble "permanent" coating on the fused silica su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
232
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(243 citation statements)
references
References 24 publications
7
232
1
1
Order By: Relevance
“…The use of polymeric coatings has led to high efficiency and reproducible protein separations preventing the surface adsorptions. Polymers ranging from highly hydrophobic to highly hydrophilic were used for this purpose to obtain efficient separations of proteins in CE [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymeric coatings has led to high efficiency and reproducible protein separations preventing the surface adsorptions. Polymers ranging from highly hydrophobic to highly hydrophilic were used for this purpose to obtain efficient separations of proteins in CE [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants had also to be added to enable the analysis of proteins in PDMS-coated FS-capillaries. The observed separation efficiencies of about 40 000 plates are, however, only moderate compared to those obtained with hydrophilic coatings in classical CE [46]. Applied to MCE it was shown that for the fluorescein-labelled goat antihuman Fab fragment a sharp peak was observed.…”
Section: Various Coatingsmentioning
confidence: 88%
“…Furthermore, a considerable suppression of analyte-wall interaction is often observed. For the suppression of protein adsorption and electroosmosis HPMC was found to be especially useful [46,47]. Accordingly, these cellulose derivatives are applicable for dynamic coating of microfluidic glass chips especially for DNA separation as they can suit as sieving buffer and for surface deactivation.…”
Section: Cellulose Derivativesmentioning
confidence: 99%
See 2 more Smart Citations